Does generativity matter? A meta-analysis on individual work outcomes. - Wiktorowicz, Justyna; Warwas, Izabela; Turek, Dariusz; Kuchciak, Iwa (European Journal of Ageing, 2022)
Ongoing demographic changes and global population ageing require organisations to pay special attention to their employment policies. With working life extension and age management increasingly included in discussions about reactive versus proactive personnel policies, the term 'generativity' gains special importance as an approach to managing a generationally diverse workforce. Generativity can be understood as an attitude of openness towards the younger generations that focuses on exchanging values, knowledge, and experiences with them. It is a source of positive emotions and better social relationships, personal fulfilment, good energy, and aliveness. In the paper, generativity is discussed in the framework of two theories: the socio-emotional selectivity theory (SST) and successful ageing theory (SOC). The aim of this paper is to assess the relationship between generativity and individual work outcomes. We considered both in-role and extra-role outcomes analysed in the job context. Meta-analysis is conducted of studies that investigate generativity and its relationships with motivational outcomes (job satisfaction, engagement, work motivation, affective commitment, self-efficacy), cognitive outcomes (attitudes toward retirement, career success, self-control), personal outcomes (wellbeing, health, job strain), relational outcomes and extra-role behaviours (organisational citizenship behaviour and sustainable behaviour). The analysis examines 65 independent samples that included 30,540 individuals, and considers the role of three moderators—the cultural context, the measurement method and age. It demonstrates that generativity has significant and positive motivational, cognitive and extra-role behaviour outcomes for workers and that it improves their well-being.